Gas flow experimental research in a newly developed centrifugal-electrostatic precipitator - Chlebnikovas, Aleksandras; Kilikevičius, Artūras (International Conference “Environmental Engineering”, 2023)
In this paper, one of the most common environmental pollution problems is investigated – air pollution with particulate matter, and the object of study is a newly created device of a hybrid type of centrifugal and electrostatic cleaning principle. These technologies are increasingly being introduced in a sequential order on past lines, but the unified model has not yet been used. The set of cleaning methods in this model allows to clean the gas flow from fine and ultra-fine particulate matter. By adopting an improved section to reduce flow turbulence, the gas flow rate has been equalized to an average of 17% to 4.6% before the inlet. Also, the designed system achieved a theoretically optimal gas flow rate of 2.2 m/s for subsequent particulate matter injection into the system of several cleaning stages. The flow before and after the purification device in the range of 1.2–2.4 m/s was also studied. The results of this work were obtained in an experimental way to analyze the dynamics of the flow in the system of the apparatus for cleaning the flow in the range from 50 to 200 m3/h, under various operating modes of this technology. The direct current in the electrostatic filter reached no more than 10 kV. The maximum gas yield is equal to 0.03 m3/s at inlet and outlet gas flow rate of 2.4 m/s and 0.77 m/s respectively, and pressure drop is up to 51 Pa.